Astragaloside IV increases PDHA1 in mesenchymal stem cell exosomes to treat myocardial infarction - Sha Zhongxin; Chen Zhijie; Du Feng; Guo Mei Qin; Zhong Ya; Hu Jinxin; Wei Zhang; Yu Zhenqiu (Scientific Reports)
Abstract Acute myocardial infarction (AMI) is a threat to health, with high morbidity and mortality, posing a challenge to the public health system. This study aimed to explore the efficacy and potential targets of Astragaloside IV (AS-IV) combined with Mesenchymal Stem Cells (MSC)-derived exosomes (Exo) in the treatment of AMI. The effect of AS-IV in treating AMI via MSC exosomes was evaluated by cardiac ultrasound to assess cardiac function, TTC staining to observe myocardial infarction area, TUNEL staining was used to analyze cell apoptosis, and ELISA to measure the IL-6 and TNF-α in myocardial tissue. Proteomics reveals the effect of AS-IV on the protein composition of MSC exosomes. Then, the mechanism of AS-IV improving MI through MSC exosomes was verified based on PDHA1 (pyruvate dehydrogenase E1 component subunit alpha). Under oxygen–glucose deprivation (OGD) conditions, the effects of silencing PDHA1 on H9c2 cells were evaluated. After completing the PDHA1-mediated AS-IV treatment of AMI through MSC exosomes, HE staining was used to analyze myocardial injury, ELISA and flow cytometry were used to detect inflammatory factors and oxidative stress levels, and WB was used to detect PDHA1 protein expression. Compared with the sham-operated group, all experimental groups showed significant damage in cardiac structural and functional indices, while AS-IV, MSC-Exo, and MSC-AS-Exo significantly improved the cardiac function in rats with acute myocardial infarction model, especially the AS-IV-treated MSC-exo group showed the best effect. Proteomic analysis showed that 106 proteins were up-regulated and 80 proteins were down-regulated in the MSC-AS-Exo group compared to the MSC-Exo group. PDHA1, as a core protein of the enrichment pathway, maybe a key protein in the therapeutic effects on MI exerted by MSC-AS-Exo. The PDHA1 is critical for the cardioprotective effects of AS-Exo, and deletion of PDHA1 significantly impaired the ameliorative effects of MSC-AS-Exo. Under OGD conditions, silencing of PDHA1 exacerbated the decreased cell proliferation ability, increased apoptosis, decreased mitochondrial membrane potential, increased reactive oxygen species (ROS) levels, and decreased ATP in H9c2 cells. Compared with MSC-AS-Exo, silencing of PDHA1 resulted in diminished protection of cardiac function, inhibited histopathological recovery, decreased antioxidant capacity, and increased inflammation in MSC-AS-Exo. In conclusion, AS-IV improves the therapeutic effect of acute myocardial infarction (AMI) by stimulating MSC to secrete Exo and enhancing the expression of pyruvate dehydrogenase α (PDHA1), and PDHA1 may be its key target.